Influence of Heliobond on Microtensile Bond Strength of a New BIS-GMA Free Versus BIS-GMA Containing Composite Resin Restoration - Elsebaey, Labib; Dowidar, Weam; Alahmed, Bader; Elmarakby, Ahmed Mohamed (Open Access Macedonian Journal of Medical Sciences, 2023)
AIM: The main objective of this study was to assess the micro-tensile bond strength (µTBS) of a free bisphenol-a-diglycidyl-ether-dimethacrylate (Bis-GMA) resin composite restorative material compared to a Bis-GMA-containing resin composite following the application of a hydrophobic coating (heliobond). MATERIALS AND METHODS: A flat occlusal dentin surface was exposed in a total of eighty extracted teeth that were removed for periodontal reasons. Teeth were divided into two main equal groups according to the type of applied filling materials: BIS-GMA-free versus BIS-GMA-containing resin composite (n = 40). Each main group was subdivided into two equal subgroups (n = 20) according to the application of Heliobond (hydrophobic resin coating). Heliobond has been applied after adhesive application and before resin composite application. The first group was restored by a Free Bis-GMA Resin Composite (Admira, Voco, Germany); the second group was restored by a Bis- GMA-containing resin composite (Grandio, Voco, Germany). Each tested restorative material was applied and cured according to the manufacturer’s instructions. RESULTS: Regardless of different composite and adhesive types, there was a statistically significant difference (p < 0.05) among all subgroups. Specimens with Heliobond recorded a higher µTBS mean value (30.46 ± 6.7 megapaskal [MPa]) than groups without Heliobond, which recorded µTBS mean value (23.95 ± 9.02 MPa). CONCLUSION: Application of an extra hydrophobic layer coating (Heliobond) has improved the performance of the µTBS of the adhesive systems utilized with the new BIS-GMA-free versus BIS-GMA-containing composite resin